Comparative Analysis of the Protective Effect of Naringenin on Cardiovascular Parameters of Normotensive and Hypertensive Rats Subjected to the Myocardial Infarction Model - Anelize Dada; Rita de Cássia Vilhena da Silva; Mariana Zanovello; Jeniffer C. Moser; Sabrina L. D. Orengo; Martina O. Cavichiolo; Eleine R. Bidinha; Thaise Boeing; Valdir Cechinel-Filho; Priscila de Souza (MDPI AG, 2024)
Background: Cardiovascular diseases rank as the top global cause of mortality, particularly acute myocardial infarction (MI). MI arises from the blockage of a coronary artery, which disrupts blood flow and results in tissue death. Among therapeutic approaches, bioactives from medicinal plants emerge as promising for the development of new medicines. Objectives: This study explored the effects of naringenin (NAR 100 mg/kg), a flavonoid found in citrus fruits, in normotensive (NTR) and spontaneously hypertensive (SHR) rats, both subjected to isoproterenol (ISO 85 mg/kg)-induced MI. Results: Post-treatment assessments indicated that NAR reduced blood pressure and minimized clot formation, particularly notable in the SHR group, which helps mitigate damage related to hypertension and ISO exposure. Additionally, NAR effectively restored KCl-induced contractility in the aortas of both NTR and SHR groups. NAR treatment reduced reduced glutathione (GSH) and lipid hydroperoxides (LOOH) values and recovered the activity of the antioxidant enzymes catalase (CAT) and glutathione-s-transferase (GST) in NTR groups. Moreover, myocardial damage assessed through histological analyses was reduced in groups treated with NAR. Conclusions: The results highlight significant pathophysiological differences between the groups, suggesting that NAR has protective potential against ISO-induced cardiac damage, warranting further investigation into its protective effects and mechanisms.